(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
Credit is considered the most important banking efficiency indicators in that its generated returns represent the main axis of any bank returns, regardless of the multiplicity and variety of other returns sources; without credit, the bank loses its main function as a financial mediator in the economy. But at the same time, it is an investment fraught with many risks due to loaning and unsuccessful facilitations. The issue of ’’Credit analysis’’ has generally become of interest to the banking activity and its workers, Given that it is an effective tool for accuracy in making credit decisions, consequently reducing the losses that banks may encounter, we have handled the process of giving credit and the process being implemented in credit facilitation in the Industrial Bank compared with the main bases of Creditory analysis; the purpose of this is to know and enhance the positive sides, and highlight the shortcomings and offer suggestions and recommendations for avoiding them in such away that contributes to guiding the processes of crediting.